Studying of the Potential Curves of Ground State of Diatomic Molecule Using Two Functions. - Atiah, Asma S.; Abdullah, Muhaj T. (Science Journal of University of Zakho, 2015)
Diatomic molecules have been studied theoretically for ground state X2Π of (CH,CO,LuF,HBr) free radicals . It had been constructed dissociation energy using potential curves for the ground state by using Morse and Varshini functions to calculate potential curve for each molecule; compared between the results and experimental values had obtained. The results have good agreement with experimental results. Finding that Varshini function approximate with experimental values more than Morse function does.